Is there a clash of civilizations? Cultures and institutions across civilizations - Masud Chand (Global Business & Finance Review (GBFR), 2022)
Purpose: We analyze how countries are similar and different in terms of cultures and institutions and the extent to which they can be grouped into civilizations. This is based on Huntington's (1993,1996) framework that states there are major cultural and institutional differences between civilizations. Design/methodology/approach: Cultural and institutional data were collected on all available countries. For culture, Hofstede index was used. For institutions, scores were used for the Index of Democracy, the Index of Economic Freedom, Freedom in the World Index, the Global Gender Gap Index, the Press Freedom Index, and the Corruption Perceptions Index. The countries were grouped along the lines of Huntington's civilizations and their scores analyzed. Findings: The results reveal that differences across civilizations are significant and extend across cultures and institutions. Across the nine civilizations, there were significant differences in five of the six cultural dimensions as well as in all the institutions. Research limitations/implications: Cultural differences across civilizations could point to pervasive differences on issues such as values, motivation, and management norms. Institutional differences across civilizations could represent differences in values that societies attach to different aspects of their institutional environment. Future studies using longitudinal data could help build on our findings. Originality/value: The use of both cultural and institutional measures to cluster countries into civilizations is a major contribution of this study. The clash of civilizations framework is analyzed relative to other studies on country clusters contributing to the discussion on supranational cultural clusters. The study would be valuable to cross-cultural researchers, international business academics and practitioners.
Keywords: 650; Civilization; Cultures; Institutions; Indices